(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Over the past twenty years, English for Specific Purposes (ESP) has evolved rapidly in China in response to economic globalization, higher education reform, and professional demands. This article provides an analytical overview of ESP research and practice in China from 2001 to 2020, identifying major themes, instructional approaches, and policy shifts. While ESP has gained substantial traction, challenges such as teacher preparedness, materials development, and assessment practices remain. The study concludes with recommendations for sustainable development and future research priorities in the Chinese ESP landscape.